Perancangan Pusat Pengembangan Kesenian dan Kebudayaan Ngawi di Kabupaten Ngawi, Jawa Timur - Dela Cahya Lestari; Putri Suryandari; Anggraeni Dyah S. (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The Ngawi Arts and Culture Development Center which is designed in Ngawi Regency is one of the districts in East Java which has various traditional arts as cultural heritage. The need for public space for the Ngawi community that can be used as a place for training or development as a preservation of arts and culture. The application of the architectural concept of regionalism can create the Ngawi Arts and Culture Development Center in Ngawi Regency, East Java which emphasizes the disclosure of the characteristics of an area to elevate the cultural locality of the community. The design center for the development of arts and culture is to support the needs and convenience of the community in the development of arts and culture of Ngawi, which is centered in the area of ​​Ngawi Regency, East Java. By applying local cultural elements to the Design of the Ngawi Arts and Culture Development Center. In accordance with regional characteristics related to climate, local culture and the incorporation of modern and local technology as the application of Regionalism Architecture. Keywords: Regionalism Architecture, Ngawi, Arts and Culture Development Center